Embryonic Development of Spinal Cord in White Choeked Bulbul (Pycnonotus leucotis) - Asmaa Basheer Abed; Aws Basheer Abed (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study concerned the embryonic development of spinal cord of white choeked bulbul Pycnonotusleucotis. The spinal cord at the age 40 hour’s incubation from the neural tube and its tissue wall is composedof two layers, the ependymal layer and mantle layer. The spinal cord differentiation is completed at the age7 day’s incubation, its, were we notice that the central canal is clear and cavity lined with neurons and wenote the arrangement of gray matter in the form of the letter H and its inside and it is characterized by dorsaland ventral horns and the gray matter substance and note the formation of dorsal medium spetum and ventralmedium fissure.